ANALISIS ANGGARAN BERBASIS KINERJA TERHADAP PELAKSANAAN PROGRAM KERJA DI DINAS PEKERJAAN UMUM KOTA PAREPARE - Sahara, Ira (Universitas Muhammadiyah Parepare, 2020)
This study aims to see the budgeting system used by the Dinas Pekerjaan Umum of Parepare City in implementing work programs. This research is qualitative, which using interviews as the required data technique. The method of analysis used is descriptive analysis method in explaining the research results from observations and interviews, with sample of research is that government officials within Dinas Pekerjaan Umum of Parepare City which have 18 structural positions. Determination of the sample using purposive sampling, which determines the sample is used due to certain considerations (time, cost, and labor limitations). The results of this study indicate that the Dinas Pekerjaan umum of Parepare City in preparing the budget using to complete existing programs is in accordance with budget preparation. So that, the budget used is accordance with performance based budgeting system that prioritizes the results and impacts of work programs that have been implemented and can help regions in making the main budget for the development of Parepare City effective and efficient, although there are still findings by auditors regarding several things that are not in accordance with reality in the field. However, it can be accounted for and improvements are made to maintain the objectives to be achieved by the Dinas Pekerjaan Umum of Parepare City.